Proceedings of the 18th Annual High Technology Small Firms Conference 2010
DOI: 10.3990/2.268474933
|View full text |Cite
|
Sign up to set email alerts
|

"Entrepreneurial Management" as a Strategic Choice in Firm Behavior: Linking it with Performance

Abstract: Establishing the core principals of “entrepreneurial management” within an organization describes a certain strategic choice that affects a company in six dimensions, according to Stevenson (1983). Our aim is to empirically measure entrepreneurial management (it’s existence and degree) and to link this measured strategic choice (for or against) entrepreneurial management with firm performance. Our argument here is that companies that follow core principals of entrepreneurial management should outperform other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…They consider growth as an essential element for short and long-term survival. This influences the businesses to pursue and exploit any available opportunity (Abker et al, 2018;Kuhn et al, 2010;Rashid & Mahmood, 2016). Research has indicated the relationship between entrepreneurial growth orientation and business performance (Kuhn et al, 2010;Rashid & Mahmood, 2016).…”
Section: Linking Entrepreneurial Management Variables To Business Per...mentioning
confidence: 99%
See 4 more Smart Citations
“…They consider growth as an essential element for short and long-term survival. This influences the businesses to pursue and exploit any available opportunity (Abker et al, 2018;Kuhn et al, 2010;Rashid & Mahmood, 2016). Research has indicated the relationship between entrepreneurial growth orientation and business performance (Kuhn et al, 2010;Rashid & Mahmood, 2016).…”
Section: Linking Entrepreneurial Management Variables To Business Per...mentioning
confidence: 99%
“…This influences the businesses to pursue and exploit any available opportunity (Abker et al, 2018;Kuhn et al, 2010;Rashid & Mahmood, 2016). Research has indicated the relationship between entrepreneurial growth orientation and business performance (Kuhn et al, 2010;Rashid & Mahmood, 2016). For example, a study from Sweden indicated that growth orientation is associated with a higher level of business performance (Bradley et al, 2011).…”
Section: Linking Entrepreneurial Management Variables To Business Per...mentioning
confidence: 99%
See 3 more Smart Citations